“FACTORS AFFECTING A SUCCESSFUL LANGUAGE LEARNER” - Nihta V. F. Liando (Indonesian JELT, 2012)
This paper reports an investigation of factors affecting a successful language learner. It describes how events throughout the learning processes support the learners in becoming successful in learning English as a second language (EFL). Data was collected from personal experiences regarding English language learning by the three student participants and three lecturer participants in the English Department Manado State University, Indonesia. Semi-structured interviews and personal narratives were used to gather the data. There were three key themes generated from the interview data: family and community, institutional influences and individual factors. The findings highlight that family members, teachers and individuals play important roles in supporting learners becoming successful in learning English.